A study on the relationship between family peer group media and career decision making among undergraduates in Nigeria - Yunusa, Salisu; Wan Jaafar, Wan Marzuki; Ismail, Asmah; Wan Othman, Wan Norhayati (Human Resource Management Academic Research Society, 2022)
This paper examines relationships between family, peer group, media and career decision making among undergraduate students in nigeria. A quantitative correlational research design was utilized. 1,200 undergraduates form the population while 373 constitute the sample size of the study. The instruments used are factors influencing undergraduate students' career decision making questionnaire with a reliability coefficient (?=.853) and career decision making self-efficacy short form questionnaire (?=.919). Structural equation modelling (sem) by using smart partial least squares (smart-pls 3.2.9) show that family and career decision making has highest significant path (t=3.828), (?=0.197) and (p=0.000) and the second highest significant path is media and career decision making (t=2.806), (?=0.129) and (p= 0.005) have significant relationship with career decision making at 0.05 level of significant. It was recommended that parents should support and endorse their children’s career choice and not to impose any career that is against their wishes. It was concluded that institutions and non-governmental organization should be organizing regular career guidance program, it will enable students to explore their interests and abilities at an early stage of adolescence that may help them make wise and realistic career decision.